2014
DOI: 10.1093/mp/ssu060
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase 4 Is a Salicylic Acid-Independent Regulator of Growth But Not of Photosynthesis in Arabidopsis

Abstract: Mitogen-activated protein kinase (MAPK) pathways regulate signal transduction from different cellular compartments and from the extracellular environment to the nucleus in all eukaryotes. One of the best-characterized MAPKs in Arabidopsis thaliana is MPK4, which was shown to be a negative regulator of systemic-acquired resistance. The mpk4 mutant accumulates salicylic acid (SA), possesses constitutive expression of pathogenesis-related (PR) genes, and has an extremely dwarf phenotype. We show that suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 79 publications
3
72
0
Order By: Relevance
“…In addition, a remarkably low number of genes deregulated in field‐grown lsd1 , in comparison to laboratory‐grown lsd1 (Wituszyńska et al ), might imply that the LSD1 suppressive role on CD is supported by other yet undetermined regulators. Potential candidates are CYSTEINE‐RICH RECEPTOR‐LIKE KINASE (Burdiak et al ), MITOGEN ACTIVATED PROTEIN KINASE 4 (Gawroński et al , Witoń et al ) and LSD ONE LIKE 1 (Epple et al ) proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a remarkably low number of genes deregulated in field‐grown lsd1 , in comparison to laboratory‐grown lsd1 (Wituszyńska et al ), might imply that the LSD1 suppressive role on CD is supported by other yet undetermined regulators. Potential candidates are CYSTEINE‐RICH RECEPTOR‐LIKE KINASE (Burdiak et al ), MITOGEN ACTIVATED PROTEIN KINASE 4 (Gawroński et al , Witoń et al ) and LSD ONE LIKE 1 (Epple et al ) proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genes such as LESION SIMULATING DISEASE1, ENHANCED DISEASE SUSCEPTIBILITY1, PHYTOALEXIN DEFICIENT4, ETHYLENE INSENSITIVE2, and MITOGEN-ACTIVATED PROTEIN KINASE 4 were shown to play important roles in the simultaneous regulation of SAA via ROSand salicylic acid-dependent pathways Szechy nska-Hebda et al, 2010;Wituszy nska et al, 2013;Gawro nski et al, 2014;for review, see Karpi nski et al, 2013;Mignolet-Spruyt et al, 2016). In addition, PHOTOSYSTEM II SUBUNIT S-dependent local and systemic wave-like regulation of nonphotochemical quenching (NPQ) and chlorophyll fluorescence decay time, important dissipation and quenching mechanisms of light absorbed in excess, were also proposed to be dependent on ROS and salicylic acid signaling during SAA (Szechy nska- Hebda et al, 2010;Gawro nski et al, 2013Gawro nski et al, , 2014Ciszak et al, 2015;Fig. 2).…”
Section: The Ros Wave Retrograde Signaling and Transcriptional Regumentioning
confidence: 99%
“…Furthermore, in atmpk4 mutants or atmpk4 / ics1 double mutants, it was shown that most of the analyzed genes encoding ROS scavenging enzymes, e.g. GR2 (encoding glutathione reductase 2), FSDs (encoding Fe-SODs), and APXs , are down-regulated, whereas CSD2 can be up-regulated [69]. The enzyme analysis demonstrated Cu/Zn-SOD and APX activities were increased whereas Fe-SOD activity was decreased in atmpk4 mutants or atmpk4 / ics1 double mutants [69] (Fig.…”
Section: Regulation Of Ros-related Genes By Mapk Cascadesmentioning
confidence: 99%